Bubbles in noodle dough: Characterization by X-ray microtomography. (March 2018) - Guillermic, R.-M.; Koksel, F.; Sun, X.; Hatcher, D.W.; Nickerson, M.T.; Belev, G.S.; Webb, M.A.; Page, J.H.; Scanlon, M.G.
Abstract: Bubbles, found in a huge variety of food products, are known to afford desirable quality attributes, especially those related to texture, mouthfeel and taste. However, the presence of bubbles and their effects on wheat flour noodles is an aspect that has been, until now, largely overlooked, despite the positive and negative connotations of bubbly inclusions on Asian noodle quality. X-rays from a synchrotron source (Biomedical Imaging and Therapy facility at the Canadian Light Source) were used to rapidly and non-destructively acquire tomographic images of noodle dough. Appropriate image analysis protocols were used to determine the bubble size distribution, the orientation of bubbles, and their position within the dough sheet. The effect of processing (one or multiple lamination steps) on bubble properties in the dough that was subsequently sheeted (gradual elongation and reduction in thickness) was investigated. Bubble size distributions, well captured by lognormal distribution function, showed that the lamination process induced bubble entrapment and reduction in bubble size. Bubbles were found to be flat, elongated and oriented in the sheeting direction, this effect being less for doughs laminated ten times (90° rotations between lamination steps). Interestingly, a gradient in concentration of bubbles within the dough sheet was found from the noodle core to the sheet edges. Aging effects were also apparent. This first non-destructive study of bubbles in wheat-flour noodle dough provides a more complete knowledge of the dough sheet's internal structure, and how it originates via processing, and this has repercussions on the overall quality of Asian noodles. Graphical abstract: Highlights: Synchrotron X-rays rapidly and non-invasively define noodle dough bubbly structure. Lamination process entraps bubbles and reduces bubble size. Bubbles concentrated towards core of dough sheet. Bubbles oriented within the dough sheet by lamination process.